Dinamika Konflik pada Perubahan Fungsi Kawasan Cagar Alam Menjadi Wisata Alam di Pulau Sempu, Kabupaten Malang - Maulana, Vivin (Universitas Brawijaya, 2022)
This study discusses the flow of development of conflict that occurred on Sempu Island. The flow of the development of this conflict involves many actors such as the surrounding community, the officials, and the tourism office. Where this conflict arises because of proposals from the community who want Sempu Island as a Nature Reserve. Here there are differences in interests where the officers follow according to the rules that Sempu Island as a Nature Reserve, then there was a conflict. This research uses descriptive qualitative methods as a tool to analyze the flow and causes of conflict in Sempu Island. This study uses the conflict flow from Kiesberg there, explained from the beginning of the conflict to the outcome of the conflict. With the conflict, conflict resolution is taken by reviewing the location of the LIPI pohak, is it really feasible as a nature tourism or not. After a review, Sempu Island was designated a Nature Reserve. Surrounding communities feel lost their jobs and they return to their original profession as farmers or fishermen.